Analysis of Laissez-Faire Leadership Style and Satisfaction Work on Employee Performance Through Motivation at Ngudi University Waluyo Ungaran Semarang Regency: Study Education Personnel Case - Fitriyanto Fitriyanto; Karnasih Karnasih (International Forum of Researchers and Lecturers, 2026)
The role of the leader must can manage pattern think source Power man For obey and carry out every work in accordance vision and mission with applicable norms and rules.​ The leaders at a organization can Possible play a role as determinant direction for source Power human and as much as possible Possible become agent change, interpreter speak and coach. Play a role whether or not a leader in make it a success organization reflected in style applied leadership​ For influence his followers. Laissez-Faire leadership is based on trust. Laissez-Faire leaders let go not quite enough answer and avoid taking decision. Research This done Because Still There is employees who have not motivated For quick finish work, as well as violation frequent discipline​ happen that is delay and check- out time frequent work​ violated. The method used in study This is study descriptive with approach quantitative purposeful​ disclose something What with sample amounting to 44 employees. The analysis tool used study This is Multiple linear regression. Research results show that style laissez-faire leadership, satisfaction work and motivation influential positive and significant to performance power Ngudi University education Waluyo Semarang Regency. Motivation No capable mediate style laissez-faire leadership, towards performance power education However motivation capable mediate satisfaction Work to performance power education.